Study guide : HBEC4303 Quality physical environment in early childhood education - Badzis, Mastura (Open University Malaysai (OUM), 2013)
This course is designed to enable you to establish a quality early childhood environment for young children, making it conducive for them to discover, invent, create and learn. it is important for children to learn in a healthy, caring, respectful and supportive environment.